Detailed analytical studies of 1,2,4-triazole derivatized quinoline - Somagond, Shilpa Mallappa; Wari, Manjunath Ningappa; Shaikh, Saba Kauser Jaweed; Inamdar, Sanjeev Ramchandra; Shankar, Madan Kumar; Prasad, Dasappa Jagadeesh; Kamble, Ravindra Ramappa (European Journal of Chemistry, 2019)
The present study describes, the X-ray single crystal analysis of 4-((2-chloro-6-methoxyquinolin-3-yl)methyl)-2-phenyl-2H-1,2,4-triazol-3(4H)-one (TMQ). The crystal data for C19H15ClN4O2: monoclinic, space group P21/n (no. 14), a = 7.3314(15) Å, b = 12.459(3) Å, c = 18.948(4) Å, β = 98.322(9)°, V = 1712.5(6) Å3, Z = 4, T = 296.15 K, μ(MoKα) = 0.245 mm-1, Dcalc = 1.423 g/cm3, 5082 reflections measured (3.926° ≤ 2Θ ≤ 38.556°), 1428 unique (Rint = 0.0545, Rsigma = 0.0574) which were used in all calculations. The final R1 was 0.0423 (I >2σ(I)) and wR2 was 0.1145 (all data). The Density functional theory optimized molecular geometries in TMQ agree closely with those obtained from crystallographic studies. The Highest Occupied Molecular Orbital (HOMO) and Lowest Unoccupied Molecular Orbital (LUMO) energy levels and energy gap were calculated by experimental (UV absorption & Cyclic voltammetry) and theoretical studies in two different solvents. The natural bond orbital analysis was performed to understand the molecular interaction on the basis of stability of molecule arising from hyper-conjugative interaction and charge delocalization. Hirshfeld surface and their related fingerprint plots enabled the identification of significant intermolecular interaction. The molecular electrostatic potential analysis provides the visual image of the chemically active sites and comparable reaction of atoms.